Optimization of the Antimicrobial Effect of Blue Light on Methicillin-Resistant Staphylococcus aureus (MRSA) In Vitro - Bumah, Violet V. (Lasers Surg Med, 2015)
BACKGROUND AND OBJECTIVE: In previous studies, we showed that irradiation with 405 nm or 470 nm light suppresses up to 92% methicillin-resistant Staphylococcus aureus (MRSA) growth in vitro and that the remaining bacteria re-colonize. In this study, the aim was to develop a protocol that yields 100% MRSA growth suppression. MATERIALS AND METHODS: We cultured 3 × 10(6) and 5 × 10(6) CFU/ml USA300 strain of MRSA and then irradiated each plate with varying fluences of 1–60 J/cm(2) of 405 nm or 470 nm light, either once or twice at 6 hours intervals. Next, we plated 7 × 10(6) CFU/ml and irradiated it with 45, 50, 55, or 60 J/cm(2) fluence, once, twice, or thrice at the same 6 hours intervals. In a third experiment, the same culture density was irradiated with 0, 165, 180, 220, or 240 J/cm(2), either once, twice, or thrice. RESULTS: Irradiation with either wavelength significantly reduced the bacterial colonies regardless of bacterial density (P < 0.05). At 3 × 10(6) CFU/ml density, nearly 40% and 50% growth of MRSA were suppressed with as little as 3 J/cm(2) of 405 nm and 470 nm wavelengths, respectively. Moreover, 100% of the colonies were suppressed with a single exposure to 55 or 60 J/cm(2) of 470 nm light or double treatment with 50, 55, or 60 J/cm(2) of 405 nm wavelength. At 5 × 10(6) CFU/ml density, irradiating twice with 50, 55, or 60 J/cm(2) of either wavelength suppressed bacterial growth completely, lower fluences did not. The denser 7 × 10(6) CFU/ml culture required higher doses to achieve 100% suppression, either one shot with 220 J/cm(2) of 470 nm light or two shots of the same dose using 405 nm. CONCLUSION: The bactericidal effect of blue light can be optimized to yield 100% bacterial growth suppression, but with relatively high fluences for dense bacterial cultures, such as 7 × 10(6) CFU/ml.